Asian mothers' risk factors for perinatal death–the same or different? A 10 year review of Leicestershire perinatal deaths. Issue 6645 (6th August 1988) - Clarke, M.; Clayton, D. G.; Mason, E. S.; MacVicar, J.
Abstract : A case-control study of all perinatal deaths in Leicestershire was established in 1976. By 1985 some 1342 singleton perinatal deaths had occurred. Perinatal mortality among patients of Asian origin was consistently higher than that among European women. Many of the sociomedical risk factors for perinatal death known at booking were common to both population groups. In this population of Asian women, however, low social class was not associated with perinatal risk and illegitimacy hardly ever occurred. In contrast, previous infertility among the Asian women was associated with risk of perinatal death, while no such association was found with European women. In 19% of perinatal deaths care was either inadequately provided or taken up. The case-control design in these circumstances provides a practicable way to evaluate causal factors and at the same time to provide information of value to educators and health service planners.